Exceptions to bed-controlled ice sheet flow and retreat from glaciated continental margins worldwide - Greenwood, Sarah L.; Simkins, Lauren M; Winsborrow, Monica; Bjarnadóttir, Lilja Rún (Science Advances, 2021)
Projections of ice sheet behavior hinge on how ice flow velocity evolves and the extent to which marine-based grounding lines are stable. Ice flow and grounding line retreat are variably governed by the coupling between the ice and underlying terrain. We ask to what degree catchment-scale bed characteristics determine ice flow and retreat, drawing on paleo-ice sheet landform imprints from 99 sites on continental shelves worldwide. We find that topographic setting has broadly steered ice flow and that the bed slope favors particular styles of retreat. However, we find exceptions to accepted “rules” of behavior: Regional topographic highs are not always an impediment to fast ice flow, retreat may proceed in a controlled, steady manner on reverse slopes and, unexpectedly, the occurrence of ice streaming is not favored on a particular geological substrate. Furthermore, once grounding line retreat is under way, readvance is rarely observed regardless of regional bed characteristics.